Asuhan Keperawatan Gerontik Pada Pasien Dengan Gastritis Dipanti Sosial Tresna Werdha Sabai Nan Aluih SicincinKabupaten Padang Pariaman - Lussia Erwinda Syam; Hasmita .; Vivi Yuderna; Sandra Dewi (CV. ITTC INDONESIA, 2026)
According to WHO data in the journal (Andari, 2023), the number of gastritis cases in the world every year is estimated to reach around 1,800,000 to 2,100,000 people. Meanwhile, in the Southeast Asian region, the incidence of gastritis is recorded as many as 583,635 cases per year from the total existing population. The purpose of this study is to provide nursing care for the elderly with gastritis at the Tresna Werdha Sabai Nan Aluih Sicincin Social Home. Gastritis is an inflammation of the gastric mucosa that can cause complaints such as heartburn, nausea, vomiting, and bloating, and can cause complications if not treated properly. The research method used was a case study by taking one patient as the research subject. The nursing care process is carried out through the stages of review, enforcement of nursing diagnosis, planning, implementation, and evaluation. The assessment will be carried out from February 11, 2026 to February 16, 2026. The results of the nursing diagnosis that emerged, namely chronic pain, fatigue, and health management were ineffective. Interventions include pain management, energy management, as well as health education and monitoring of patient conditions. After undergoing the application for 5 days, results were obtained that showed a reduction in pain, energy after rest, and an improvement in the patient's ability to manage their health. It is hoped that patients can maintain a healthy lifestyle, regulate their diet regularly, avoid foods that trigger gastritis, and regularly carry out health checkups so that the condition does not recur.